Physicochemical Properties of Hybrid Biodegradable Silica-Hydrogel Composites - Filho, Adhemar Watanuki [UNESP]; Yonezawa, Uilian Gabaldi [UNESP]; de Moura, Marcia Regina [UNESP]; Aouada, Fauze Ahmad [UNESP] (FapUNIFESP (SciELO), 2023)
Hydrogels based on polyacrylamide, carboxymethylcellulose and silica are composites with good absorption and release properties over time, and this behavior allow their application in several areas. Thus, the aim of study was to analyze the absorption kinetic, spectroscopic, morphological, and structural properties of hydrogels prepared using different silica concentrations (0, 0.5, and 2.5%). The results showed that the swelling degree reduces with increasing silica, i.e., there was increase in crosslinking density, which was confirmed by SEM images. The reductions in the swelling degrees at equilibrium were 26.19% (0.50% silica) and 22.02% (2.5% silica) when compared to PAAm+CMC hydrogel. FTIR spectra showed characteristic spectroscopic bands of silica between 1384 and 1120 cm-1 indicating that its incorporation into the hydrogel matrix has occurred, which was also observedin the XRD diffractograms. Thus, the study of biodegradable hybrid hydrogels is relevant because theycan potentially be applied in areas such as agriculture, tissue engineering and even civil construction.
Keywords: Composite; hydrogel; polymer absorbent; silica